Pengaruh Pendidikan Pancasila Terhadap Sikap Nasionalisme Mahasiswa Baru Jurusan Pendidikan Akuntansi Universitas Negeri Makassar - Dini Fatrika Sari; Nur Hikmah; Halimatuzzahrah Halimatuzzahrah; Sri Wulandari; Nabila Azzahra; Nadia Nadia (PT. Citra Media Publishing, 2025)
This study aims to examine the extent of the influence of Pancasila Education course on the formation of a nationalist attitude in new students of the Accounting Education Department at Makassar State University. Pancasila education is seen as an important means in instilling national values to students who will serve as well as national leaders. This research used a qualitative approach with data collection methods through semi-structured interviews to students who had attended the course. Findings indicate that Pancasila Education has a positive impact on increasing students’ nationalist attitudes. However, there are several obstacles, such as learning approaches that tend to be theoretical and lack example in everyday life. Therefore, learning is recommended to be more contextual and inspiring so that Pancasila values are easier to apply.